Kajian Etnobotani Tanaman Kencur (Kaempferia galanga) di Desa Majakerta, Kecamatan Majalaya, Kabupaten Bandung (International Forum of Researchers and Lecturers, 2024)
Galangal (Kaempferia galanga L) is a plant in the Zingiberaceae family. Galangal is known as a famous traditional medicine in ancient times, kencur is generally used as a medicine for sore throats. Galangal can also be used as a medicine for bloating which can be used by pounding it first or can be consumed directly by chewing. Galangal can be processed first into traditional herbal medicine (kencur rice), processing kencur into traditional herbal medicine itself requires several other additional ingredients, as for the processing method, the galangal rhizome and ginger are washed first, then ground until soft and smooth. Then roast the rice flour and cinnamon, and wash the cardamom and then mash it until smooth, then squeeze it and then extract the juice. Majakerta is a sub-district located in Majalaya sub-district, apart from Majakerta in Majalaya there are also several other sub-districts, namely Biru, Bojong, Majasetra, Neglasari, Padamulya, Padaulu, Sukamaju, Sukamukti, Wangisagara, Cipaku, Rajadesa, and Drawati.